Rancangan Bangun Aplikasi Sales Data Collection System Berbasis Website : Studi Kasus Pada PT Anugerah Raja Terkini - Mulyana, Ade; Hermawan, Yanto (Jurnal Informatika Kesatuan, 2023)
Megmilk Snow Brand Indonesia is a company that produces milk-based foods (cheese processing) with the well-known brand MEG Cheese. PT Anugerah Raja Terkini is one of the outsourcing companies that collaborates with PT. Megmilk Snow Brand Indonesia. PT Anugerah Raja Terkini itself is responsible for sales activities at the Sales Promotion Girl level. Currently, PT. Anugerah Raja Terkini monitors its SPG only using WhatsApp media. PT. Anugerah Raja Terkini cannot confirm whether the sales are genuine or fictitious, and the admin takes a relatively long time to create a sales report. To be able to overcome this problem, an information system is needed that can support sales data collection activities at PT. Recent King's Awards. The aim of this data collection system is that sales personnel can work better and the sales reporting process can run more quickly and accurately. Keywords: application, sales data, data collection, system